Red blood cells from patients with sitosterolemia exhibit impaired membrane lipid composition and distribution and decreased deformability - Cloos, Anne-Sophie; Rab, Minke A. E.; Van Der Smissen, Patrick; van Oirschot, Brigitte A.; Mignolet, Eric; van der Net, Jeroen B.; Koster, Ad; Kleinen, Kelly; Larondelle, Yvan; Terrasi, Romano; Muccioli, Giulio G.; van Wijk, Richard; et al. (Frontiers in Hematology, 2023)
Sitosterolemia is a metabolic disorder leading to excessive accumulation of phytosterols. Hemolytic stomatocytosis and macrothrombocytopenia are part of the clinical picture. However, the impact of phytosterols on red blood cell (RBC) deformability, membrane lipid composition and distribution and the efficiency of the reference treatment, Ezetimibe, are largely unknown. This study addresses these issues using RBCs from three patients with sitosterolemia and healthy RBCs exposed to β-sitosterol. Patients presented an increased proportion of stomatocytes, decreased RBC deformability and increased RBC hydration and osmotic fragility compared to healthy donors. At the membrane level, patient RBCs showed (i) very high content in β-sitosterols, (ii) increased proportions of saturated fatty acids and polyunsaturated fatty acid species with long and unsaturated carbon chains, and (iii) decreased content in phosphatidylethanolamine species. These lipid changes were accompanied by an almost complete abrogation of cholesterol-enriched domains, which could result from: (i) the reduced phosphatidylethanolamine content which positively correlated with domain abundance; and (ii) the fatty acid modifications and increased phytosterol content, both compatible with higher membrane stiffness. The role of β-sitosterol was supported by comparable changes in RBC morphology and cholesterol-enriched domains upon β-sitosterol integration at the healthy RBC membrane. Finally, Ezetimibe treatment combined with a restricted diet lowered phytosterols and improved anemia and RBC deformability and hydration. However, this treatment had no or limited effect on RBC morphology and cholesterol-enriched domain abundance. This study reveals for the first time that phytosterols affect RBC membrane lipid composition and distribution but also RBC morphology, hydration, deformability and fragility.